A new multi-agent particle swarm algorithm based on birds accents for the 3D indoor deployment problem. (August 2019) - Mnasri, Sami; Nasri, Nejah; van den Bossche, Adrien; Val, Thierry
Abstract: The 3D indoor deployment of sensor nodes is a complex real world problem, proven to be NP-hard and difficult to resolve using classical methods. In this context, we propose a hybrid approach relying on a novel bird's accent-based many objective particle swarm optimization algorithm (named acMaPSO) to resolve the problem of 3D indoor deployment on the Internet of Things collection networks. The new concept of bird's accent is presented to assess the search ability of particles in their local areas. To conserve the diversity of the population during searching, particles are separated into different accent groups by their regional habitation and are classified into different categories of birds/particles in each cluster according to their common manner of singing. A particle in an accent-group can select other particles as its neighbors from its group or from other groups (which sing differently) if the selected particles have the same expertise in singing or are less experienced compared to this particle. To allow the search escaping from local optima, the most expert particles (parents) "die" and are regularly replaced by a novice (newborn) randomly generated ones. Moreover, the hybridization of the proposed acMaPSO algorithm with multi-agent systems is suggested. The new variant (named acMaMaPSO) takes advantage of the distribution and interactivity of particle agents. Experimental, numerical and statistical found results show the effectiveness of the two proposed variants compared to different other recent state-of-the-art of many-objective evolutionary algorithms. Highlights: Proving the efficiency of optimization algorithms in solving real-world problems. A new concept of accent birds introduced to the particle swarm optimization. A new hybrid scheme that integrates PSO and MAS. The hybridization improves the performance of the original tested algorithms. A comparison between simulation and experimental validation is given.